2009
DOI: 10.1007/s11999-008-0696-3
|View full text |Cite
|
Sign up to set email alerts
|

Transtrochanteric Rotational Osteotomy for Nontraumatic Osteonecrosis of the Femoral Head in Young Adults

Abstract: Transtrochanteric rotational osteotomy (TRO) is a controversial procedure with reported inconsistent results. We reviewed 50 patients (60 hips) who underwent this procedure for extensive osteonecrosis of the femoral head, focusing on varization to determine its effectiveness as a head-preserving procedure in young adults. The mean age of the patients was 28 years (range, 18-46 years). Using the Ficat-Arlet classification, 40 hips had Stage II and 20 hips had Stage III involvement. According to the classificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Evidence has shown that small, medially located, asymptomatic lesions may be treated with observation alone, whereas the recommended options for symptomatic precollapse stage lesions are decompression 7,86-90 , osteotomy [91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108] , and non-vascularized or vascularized bone-grafting 90,[109][110][111] . Once the early postcollapse stage is reached, total hip arthroplasty provides consistent results; however, satisfactory results have also been demonstrated with bone-grafting [112][113][114][115][116][117][118][119][120][121][122][123][124][125] .…”
Section: Table II Decision-making Hierarchymentioning
confidence: 99%
“…Evidence has shown that small, medially located, asymptomatic lesions may be treated with observation alone, whereas the recommended options for symptomatic precollapse stage lesions are decompression 7,86-90 , osteotomy [91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108] , and non-vascularized or vascularized bone-grafting 90,[109][110][111] . Once the early postcollapse stage is reached, total hip arthroplasty provides consistent results; however, satisfactory results have also been demonstrated with bone-grafting [112][113][114][115][116][117][118][119][120][121][122][123][124][125] .…”
Section: Table II Decision-making Hierarchymentioning
confidence: 99%
“…These previous operations can result in increased operative time, increased blood loss, malpositioning of implants, special removal equipment, and intraoperative osteotomies and potential compromise of long-term implant survival [82][83][84].…”
Section: Total Hip Arthroplastymentioning
confidence: 99%
“…Transtrochanteric rotational osteotomy has historically demonstrated variable success for avoidance of femoral head collapse [43,45,81] . Exploration of the risk factors revealed that higher age, higher BMI, and higher stages of osteonecrosis were determinants of likelihood of conversion of osteotomies to THA [82] .…”
Section: Update On Bench Research and Clinical Applicationsmentioning
confidence: 99%